Heavily aluminated graphene nanoplatelets as an efficient flame-retardant. (May 2017) - Jeon, In-Yup; Shin, Sun-Hee; Choi, Hyun-Jung; Yu, Soo-Young; Jung, Sun-Min; Baek, Jong-Beom
Abstract: Substantial amounts of aluminum (Al), which is one of the most abundant elements and period III post-transition metals, can be incorporated into graphene nanoplatelets (GnPs) by ball-milling graphite in the presence of solid Al beads. After thoroughly etching away any unreacted Al residues, the structure and properties of the resultant aluminated GnPs (AlGnPs) were characterized using various analytical techniques including transmission electron microscopy (TEM) and time-of-flight secondary ion mass spectroscopy (TOF-SIMS). The results indicate that AlGnPs contain a considerable amount of Al (30.9 wt%, by TEM energy dispersive X-ray spectrum) and display good dispersibility in various solvents, including water. Next, composite films from aqueous AlGnP/poly(vinyl alcohol) (1/4, wt/wt) solutions were cast and tested for flame retardation. The results indicate that AlGnPs could serve as an outstanding flame retardant that operates by both chemical (condensation) and physical (cooling and blocking) mechanisms. This suggests that AlGnPs may provide a promising option for a new, cost-effective, eco-friendly, yet efficient flame retardant. Graphical abstract: Heavily aluminated graphene nanoplatelets (AlGnPs) are produced by mechanochemical ball-milling of graphite with solid aluminum beads. AlGnPs show outstanding flame retardancy via chemical and physical flame retardation mechanisms. Hence, AlGnPs provide a very promising option for cost-effective, eco-friendly, efficient flame retardants.